Application of Red Ginger Compress in Gout Patients in Families to Reducing Chronic pain in Padang City: Case Study - Ayunisri, Dea; Astuti, Verra Widhi; Tasman, Tasman; Amri, Lola Felnanda (Fakultas Kedokteran, 2024)
Gout can interfere with a person's comfort in doing activities due to joint pain and can also trigger complications such as kidney failure or kidney stones. The incidence of gout in the world is increasing from year to year. Gout treatment can be done with and without drugs. Non-drug therapy that can be used to relieve gout pain is red ginger warm compress therapy. This study aims to determine red ginger warm compress therapy to relieve pain in gout sufferers. This study uses a descriptive design with a case study of nursing care using red ginger warm compress therapy in gout sufferers. The respondents selected were 2 adult gout sufferers from 2 families. Measurement of pain levels using the Numerical Rating Scale (NRS). Pain measurements were taken before and after giving red ginger warm compresses for 15 minutes for 7 days. After receiving warm compress treatment using red ginger, the pain levels in both people decreased by an average of 4.35. Applying red ginger warm compresses helps relieve pain in gout sufferers. This therapy can be used by health workers as a complementary therapy in gout patients.